A Comparative study of online and traditional (face to face) learning - Fatima, Sumia; Idrees, Tayyaba; Hamid, Sidra; Umar, Muhammad (Journal of Rawalpindi Medical College, 2022)
Introduction: Ever since the advent of usage of internet as a medium of teaching in late 1980s, the method of distanced teaching using online methods has been on the rise.We did a comparative study of online vs. Traditional learning in order to assess student’s viewpoint about the different ways of learning and to assess various aspects of online classes when compared with physical classes Materials and Methods: A cross sectional, descriptive study was conducted in may-june 2021 in –removed for blind review—in order to analyse the response of students towards the online mode of learning, and compare it with the traditional learning. The target population were the students of 1st, 2nd and 3 year MBBS at the Rawalpindi Medical University. Self structured questionnaires were disributed among a total of 600 students, 200 students from each year. The data collected was analysed using SPSS v 22 and using chi square test. Results: 87% (522 out of 600) students responded that traditional learning is more effective as compared to online learning. It was shown that there is no association between year of study and mode of learning also no association between gender and mode of learning. Weak internet connection is the biggest hurdle to online learning. Discussion and Conclusions: Majority of the participants, acknowledging the positive aspects of online learning; like making management of assignments easier,promoting creativity, easier access to contents and facilitation of giving feedback, still favoured traditional, face-to-face learning, for it ensures a better study environment, allows adequate clinical practice, and improves interaction with the teacher and the fellow students. The biggest hurdles to online learning were connectivity issues, lack of technical expertise, and the need for stricter self-discipline. In short,with removal of the problems associated with online learning, it can evolve into an efficient mode of learning in the near future. Key words: Educational technology; Higher education, Online learning, traditional learning, interaction Word Count Of Abstract : 299